Socio-Cultural Factors in Family Food Selection in Indonesia: A Literature Review - Tasya, Tasya (Journal Nutrizione, 2025)
This study is a qualitative review based on literature studies on strategies for overcoming malnutrition in children under five in rural areas. Through data collection from journals, reports, and policy documents published in 2020–2025, a thematic analysis was conducted to identify root causes, good practices, and intervention gaps. The findings show that malnutrition in children under five in rural areas is triggered by poverty and low family food security, minimal nutritional literacy among parents, and limited infrastructure and primary health services. Effective strategies revealed include community-based nutrition education, utilization of local foods, cross-sector interventions, and culturally sensitive communication utilizing local figures and local media. The involvement of health cadres, community leaders, and family economic empowerment has been shown to increase program sustainability. This study recommends a holistic policy that integrates education, economic empowerment, strengthening health services, and local cultural adaptation to reduce the prevalence of malnutrition in children under five in villages. The main contribution of this study is the development of a strategic framework based on evidence and local context that can be used as a reference for policy makers and public health practitioners.